Evaluation of anticancer activities of chistia vespertilionis (red butterfly wing) on breast cancer. - Sean Ng, Chee Hang (2025)
Christia vespertilionis, commonly referred to as the "Red Butterfly Wing," belongs to the Fabaceae family and is widely recognized for its therapeutic potential in traditional medicine, particularly for its anti-inflammatory, antioxidant, and anticancer properties. This study investigates the anticancer effects of methanol and hexane extracts derived from the leaves of Christia vespertilionis on MCF-7 human breast cancer cells. The plant extracts were obtained through maceration and subsequently analyzed to determine their phytochemical content, including phenolics, tannins and flavonoids which are known to possess anticancer properties. The inhibition percentage of the extracts was assessed using a CCK-8 assay, testing concentrations of 5, 50, 100, and 200 μg/mL over 24, 48, and 72 hours. The hexane extract demonstrated significant anticancer activity, with mean cell viability percentages of 81.0% (24 hours), 72.9% (48 hours), and 71.3% (72 hours) at the concentration of 100 μg/mL The methanol extract of 200 μg/mL concentration exhibited moderate activity, with corresponding cell viability percentages of 82.8% (24 hours), 77.5% (48 hours), and 83.2% (72 hours). Inhibition percentages for the hexane extract at 100 μg/mL concentration was 25% averagely, highlighting its superior efficacy compared to the methanol extract at 200 μg/mL concentration, which achieved a average inhibition of 18.8%. Phytochemical analysis via Gas Chromatography-Mass Spectrometry (GC-MS) identified key compounds such as phenolic acids, flavonoids, and long-chain alcohols, which are associated with anticancer and antiproliferative effects. The study concludes that Christia vespertilionis, particularly its hexane extract, exhibits strong anticancer potential against MCF-7 cells. These findings ensures Christia vespertilionis is a promising natural anticancer agents, supporting further investigation into the isolation of bioactive compounds, their mechanisms of action, and in-vivo validation of efficacy and safety.